EQUIPAMENTOS OLÍMPICOS: UM ESTUDO EXPLORATÓRIO ENVOLVENDO LOCALIZAÇÃO E USOS PÓS-JOGOS - Silva, Gabriela Costa da; Reis, Antônio Tarcísio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this paper is to investigate the relationship between the location of different types of Olympic equipment and their post-Olympic Games' uses in Rio de Janeiro. The areas chosen for the study are Deodoro and Barra da Tijuca, because they had the largest number of Olympic venues. Data gathering means included interviews with three groups of users: workers at Olympic areas, residents of Olympic areas and users of Olympic areas and their surroundings that do not live nearby, totaling 113 interviews. Data analysis was performed according to the frequency, content and importance of the points mentioned by the interviewees. The main results reveal problems regarding the use and the location of Olympic equipment in the two areas of the city, for example, regarding the fact that some equipment are not used by people living in nearby areas.